Coercive compliance? Anti-doping systems in tennis and athlete mental health - Colangelo, Jill; Smith, Alexander; Claussen, Malte Christian; Castaldelli-Maia, Joao Mauricio; Liebrenz, Michael (Frontiers in Sports and Active Living, 2025)
Recently, a group of professional tennis players (i.e., the Professional Tennis Players Association) filed a legal case against several governing bodies in the sport. This suit intends to challenge the alleged disregard for athlete wellbeing when enforcing anti-doping policy, as this can engender adverse effects even in unintentional or unproven cases. This complaint is set against the background of several high-profile doping proceedings in tennis, which have further revealed potential inconsistencies in integrity investigations and processes. Accordingly, the purpose of this article is to explore the possibly harmful conditions for athletes described in this litigation, as well as to acknowledge the need for multi-faceted support among professional players. In doing so, this perspective paper also draws attention to the need for fairness in professional sport, alongside proposing ways in which sport psychiatrists and sports medicine physicians can advise and advocate for education for players, other healthcare specialists, and governing bodies.